Recent trends in the Southern Ocean eddy field. Issue 1 (21st January 2015) - Hogg, Andrew McC.; Meredith, Michael P.; Chambers, Don P.; Abrahamsen, E. Povl; Hughes, Chris W.; Morrison, Adele K.
Abstract Eddies in the Southern Ocean act to moderate the response of the Antarctic Circumpolar Current (ACC) to changes in forcing. An updated analysis of the Southern Ocean satellite altimetry record indicates an increase in eddy kinetic energy (EKE) in recent decades, contemporaneous with a probable decrease in ACC transport. The EKE trend is largest in the Pacific (14.9 ± 4.1 cm2 s−2 per decade) and Indian (18.3 ± 5.1 cm2 s−2 per decade) sectors of the Southern Ocean. We test the hypothesis that variations in wind stress can account for the observed EKE trends using perturbation experiments conducted with idealized high‐resolution ocean models. The decadal increase in EKE is most likely due to continuing increases in the wind stress over the Southern Ocean, albeit with considerable interannual variability superposed. ACC transport correlates well with wind stress on these interannual time scales, but is weakly affected by wind forcing at longer periods. The increasing intensity of the Southern Ocean eddy field has implications for overturning circulation, carbon cycling, and climate.